Permaculture as Theo-drama in the Multispecies Commons: Holmgren’s Permaculture as Performance for Deane-Drummond’s Ecotheology - Bierma, Troy (Journal of reformed theology, 2025)
This article limits itself to a selection of key ideas on animal ethics from Celia Deane-Drummond’s ecotheology. She has been generally cautious about venturing into ethical implications of her ecotheology. The result is that her robust theological reflection remains rather open-ended for practicing growth in virtue. I juxtapose some of her key ideas with David Holmgren’s permaculture approach to animals to investigate how far permaculture can guide the performance of Deane-Drummond’s normative concerns. Permaculture is a design science for applying insights from ecology as an applied environmental ethic. I argue that Holmgren’s permaculture can guide a virtuous practice of Deane-Drummond’s animal ethics and lends itself as a context for ecotheological reflection. How can permaculture develop our ability to risk identifying and taking ethical environmental actions with relation to animals? What fruit might be borne for our own growth in virtue through the practice of permaculture’s approach to animals?